Social Anxiety Viewed From Self-Esteem In Adolescents Low Socio-Economic Status: Kecemasan Sosial Ditinjau Dari Harga Diri Pada Remaja Status Sosial Ekonomi Rendah - Pratiwi, Deby (Psikologia : Jurnal Psikologi, 2019)
This study aims to determine the relationship between self esteem with social anxiety. The subjects of this study were 115 adolescents in low socioeconomic status of Lingkungan VIII Belawan I, kecamatan Medan-Belawan. Datas were obtained from scales used to measure self esteem and social anxiety. Calculations were performed by testing the analysis requirements (assumption) that consisted of tests for normality and linearity. The data were analyzed using Product Moment Correlation with SPSS 17 for Windows. The results of the data analysis showed that the correlation coefficient was - 0.595 with a significance value of 0.000 (p <0.05). It showed that there is a negative relationship between self esteem and social anxiety. The results of this study indicate that the contributions made by the variable of self esteem on social anxiety was 35.5 percent, while the remaining 64.5 percent was influenced by other factors that were not examined. From these results, it is concluded that the hypothesis, which stated that there is a negative relationship between the self esteem and social anxiety, is acceptable.